(m+3n)(6m-5n)=0

Simple and best practice solution for (m+3n)(6m-5n)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (m+3n)(6m-5n)=0 equation:


Simplifying
(m + 3n)(6m + -5n) = 0

Multiply (m + 3n) * (6m + -5n)
(m(6m + -5n) + 3n * (6m + -5n)) = 0
((6m * m + -5n * m) + 3n * (6m + -5n)) = 0

Reorder the terms:
((-5mn + 6m2) + 3n * (6m + -5n)) = 0
((-5mn + 6m2) + 3n * (6m + -5n)) = 0
(-5mn + 6m2 + (6m * 3n + -5n * 3n)) = 0
(-5mn + 6m2 + (18mn + -15n2)) = 0

Reorder the terms:
(-5mn + 18mn + 6m2 + -15n2) = 0

Combine like terms: -5mn + 18mn = 13mn
(13mn + 6m2 + -15n2) = 0

Solving
13mn + 6m2 + -15n2 = 0

Solving for variable 'm'.

Factor a trinomial.
(6m + -5n)(m + 3n) = 0

Subproblem 1

Set the factor '(6m + -5n)' equal to zero and attempt to solve: Simplifying 6m + -5n = 0 Solving 6m + -5n = 0 Move all terms containing m to the left, all other terms to the right. Add '5n' to each side of the equation. 6m + -5n + 5n = 0 + 5n Combine like terms: -5n + 5n = 0 6m + 0 = 0 + 5n 6m = 0 + 5n Remove the zero: 6m = 5n Divide each side by '6'. m = 0.8333333333n Simplifying m = 0.8333333333n

Subproblem 2

Set the factor '(m + 3n)' equal to zero and attempt to solve: Simplifying m + 3n = 0 Solving m + 3n = 0 Move all terms containing m to the left, all other terms to the right. Add '-3n' to each side of the equation. m + 3n + -3n = 0 + -3n Combine like terms: 3n + -3n = 0 m + 0 = 0 + -3n m = 0 + -3n Remove the zero: m = -3n Simplifying m = -3n

Solution

m = {0.8333333333n, -3n}

See similar equations:

| x-(3x+7)=-5 | | x=24x^3-28x^2+8x | | 5x+y+0=3 | | 1=-0.25n+1 | | 5x-3(x-3)=-17 | | (x-8)+(5x)=(9x-80) | | 14=5n+4+5n | | 7(x+5)+6(x-1)=-10 | | 3.9-30= | | X-4-20x=-2 | | 6x^2-4x-20=14 | | X+3*4= | | X^2+13x+36=36 | | 54=27x | | 2x-4+12=8(x+1-2x) | | 45/(4+1)=18-49*(3+2) | | 5x+y+3=3 | | 4t^2-4t-8=0 | | 2y+x=110fory | | c=5a+b | | 2(x+6)=4(x+2.6) | | x-.4=.4x | | 45/(4+1)= | | -4(5a-10)=0 | | f(x)=27x | | 60c-54c+108=0 | | 2x-4+12=8(x+1)-2x | | x^2+169-12=0 | | -5+7(x+6)=x+37 | | (x+2)4=8 | | 15x^2+16x+7=0 | | 33-(x+5)=8x-8 |

Equations solver categories